Novice to expert: building your skillset / Nur Ida Aniza Rusli ... [et al.] - Rusli, Nur Ida Aniza; Yaacob, Nurul Aityqah; lsmail, Norul Fadhilah; Tuan Zakaria, Tuan Norhafizah; Ramli, lntan Syaherra; Zulkifle, Farizuwana Akma; Ahmad, Siti Noor Dina; Mahayadin, Mahfuzah; Mohamed, Nadiah; Mohd Taib, Jamaliah; Mohd Ruslan, Siti Zaharah; Andu, Yusrina; et al. (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Student mobility stands as a strategic approach in cultivating dynamic and versatile students. It aims to provide opportunities for students to participate in global academic programs, exposing them to novel environments, experience diversity of cultures, broadening their global social networks, and enrich their overall educational experiences. Thus, to achieve one of the performance indicators outlined in the UiTM2023 strategic plan, the College of Computing, Informatics, and Mathematics, UiTM Cawangan Negeri Sembilan (UiTMCNS), in collaboration with Universitas Islam Negeri Sultan Syarif Kasim Riau (UIN SUSKA), initiated a student mobility program called "Workshop Novice to Expert: Building Your Skillset". The program, which comprised six series of webinars conducted from April 15 to June 17, 2023, was designed to cover a variety of topics, all of which were directly related to cutting-edge research and emerging trends in the field of computer science and mathematics.